MAPPING OF THE TRIGGER VARIABLES OF DISTRIBUTION OF INCOME DISTRIBUTION IN ACEH PROVINCE BEFORE AND AFTER THE COVID-19 PANDEMIC - Andriyani , Devi; Nailufar , Fanny; Anwar , Khairil; Cut Tiara Rizki (CV. Radja Publika, 2022)
The income distribution gap (KDP) between regions is an unavoidable reality in both developed and developing countries, and is a major concern during the pandemic. The COVID-19 pandemic that has emerged since 2019, has caused governments in various countries to set various policies to deal with the virus, which has hampered and restricted the economic activities of the community, resulting in higher KDP and dependence on the government. The higher the KDP number, it can indicate the condition of uneven economic development in each region. In addition, each region has the characteristics of different economic problems, therefore strategic policies are needed for each region to be able to overcome regional problems. This strategic policy is also expected to overcome economic disparities between regions. So that strategic policies can be formulated properly and appropriately, it is necessary to conduct research on macroeconomic variables that affect the KDP of each region. This study aims to analyze how big the gap in income distribution between regions in districts/cities in Aceh Province is and how big the influence of the variables of Gross Regional Domestic Product (GRDP), population and open unemployment rate (TPT) on KDP in districts/cities in the province. Aceh before and after the covid-19 pandemic. The research was conducted by calculating the Williamson Index to determine the size of the income gap between regions, and the data analysis model using the panel data regression model. The results of the Williamson index calculation show that KDP in the district / city of Aceh Province during the pre-pandemic period was in the low category and increased in the post-pandemic period. Even some areas such as Aceh Besar, North Aceh and Bireuen, the KDP is in the moderate category during the pandemic. The results of the regression analysis show that GRDP does not have a dominant effect on KDP districts/cities in Aceh Province before and after the covid 19 pandemic. Meanwhile, Population and TPT have a positive and significant effect on districts/cities in Aceh Province before and after the covid 19 pandemic. Results Gini ratio constant calculation shows that Langsa is the city with the largest Gini Ratio value from other regions,